Chapter 1: the archaeology of rivers: processes and patterns - Campbell, Peter B. (Taylor & Francis, 2023)
The archaeology of rivers to date could be categorized as archaeology in rivers, rather than an archaeology of rivers. Rivers are dynamic entities which form complex entanglements with cultures. However, rivers follow natural processes, and their geomorphology has an elegant underlying structure. These processes lead to cultural patterns that are entangled with the river’s agency, though humans are likewise agents. This chapter examines these processes (e.g. upland/lowland rivers, thalweg, riffle and pool sequences) and the patterns (e.g. settlements, navigation, bridge design) that relate to them. It advocates for an archaeology of rivers which makes use of both terrestrial and submerged information to understand the broader context of riverine cultures.